52 Proceedings and Acts of the General Assembly, 1755-1756, at 458 (1935) - (:unkn) unknown (My University, 1756)
Kept the militia age at 16 to 60. This act changed the ammunition requirement to "nine Charges of Gun-powder and nine Sizeable Bulletts." Troopers needed to provide themselves with "a pair of good Pistols a good Sword or Hanger half a pound of Gun-powder and twelve Sizeable Bulletts and a Carbine --well fixed with a good Belt Swivel and Buckett."
Keywords: MILITIAS